The Effects of using the self- esteem Development Program and Emotional Intelligence on Moral Behavior of Roi Et Rajabhat University Students - Sripongplerd, Prasarn (Journal of Roi Et Rajabhat University, 2021)
The purposes of this research were 1) to study the level of moral behavior of Roi Et Rajabhat University students, and 2) to compare the effects of using the self-esteem development program and emotional intelligence on moral behavior of Roi Et Rajabhat University students between before and after the experiment. The population were 367 students of the 1st- 4th year in the bachelor’s degree program of social studies, faculty of education, Roi Et Rajabhat University. The samples used in the experiment were 28 students in the 2nd year of social studies. The research instruments consisted of 1) Moral Behavior Test 2) Program to develop self-esteem and emotional intelligence. Data were analyzed by using t-test for dependent samples. The results showed that: 1) Roi Et Rajabhat University students have moral behavior at a high level. 2) After participated the self-esteem development program and emotional intelligence, found that scores of moral behaviors in overall and in each aspect were significantly increased at the .05 level.